The Intracellular Cleavage Product of the NG2 Proteoglycan Modulates Translation and Cell-Cycle Kinetics via Effects on mTORC1/FMRP Signaling - Nayak, Tanmoyita; Trotter, Jacqueline; Sakry, Dominik (Frontiers in Cellular Neuroscience, 2018)
The NG2 proteoglycan is expressed by oligodendrocyte precursor cells (OPCs) and is abundantly expressed by tumors such as melanoma and glioblastoma. Functions of NG2 include an influence on proliferation, migration and neuromodulation. Similar to other type-1 transmembrane proteins, NG2 undergoes proteolysis, generating a large ectodomain, a C-terminal fragment (CTF) and an intracellular domain (ICD) via sequential action of α- and γ-secretases which is enhanced by neuronal activity. Functional roles of NG2 have so far been shown for the full-length protein, the released ectodomain and CTF, but not for the ICD. In this study, we characterized the role of the NG2 ICD in OPC and Human Embryonic Kidney (HEK) cells. Overexpressed ICD is predominantly localised in the cell cytosol, including the distal processes of OPCs. Nuclear localisation of a fraction of the ICD is dependent on Nuclear Localisation Signals. Immunoprecipitation and Mass Spectrometry followed by functional analysis indicated that the NG2 ICD modulates mRNA translation and cell-cycle kinetics. In OPCs and HEK cells, ICD overexpression results in an mTORC1-dependent upregulation of translation, as well as a shift of the cell population towards S-phase. NG2 ICD increases the active (phosphorylated) form of mTOR and modulates downstream signalling cascades, including increased phosphorylation of p70S6K1 and increased expression of eEF2. Strikingly, levels of FMRP, an RNA-binding protein that is regulated by mTOR/p70S6K1/eEF2 were decreased. In neurons FMRP acts as a translational repressor under activity-dependent control and is mutated in Fragile X Syndrome (FXS). Knock-down of endogenous NG2 in primary OPC reduced translation and mTOR/p70S6K1 phosphorylation in Oli-neu. Here, we identify the NG2 ICD as a regulator of translation in OPCs via modulation of the well-established mTORC1 pathway. We show that FXS-related FMRP signalling is not exclusive to neurons but plays a role in OPCs. This provides a signal cascade in OPC which can be influenced by the neuronal network, since the NG2 ICD has been shown to be generated by constitutive as well as activity-dependent cleavage. Our results also elucidate a possible role of NG2 in tumors exhibiting enhanced rates of translation and rapid cell cycle kinetics.